If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + 6z + -1y + -1x + 12y + 4z + -6z + 2y + -11x = 0 Reorder the terms: -7x + -1x + -11x + -1y + 12y + 2y + 6z + 4z + -6z = 0 Combine like terms: -7x + -1x = -8x -8x + -11x + -1y + 12y + 2y + 6z + 4z + -6z = 0 Combine like terms: -8x + -11x = -19x -19x + -1y + 12y + 2y + 6z + 4z + -6z = 0 Combine like terms: -1y + 12y = 11y -19x + 11y + 2y + 6z + 4z + -6z = 0 Combine like terms: 11y + 2y = 13y -19x + 13y + 6z + 4z + -6z = 0 Combine like terms: 6z + 4z = 10z -19x + 13y + 10z + -6z = 0 Combine like terms: 10z + -6z = 4z -19x + 13y + 4z = 0 Solving -19x + 13y + 4z = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13y' to each side of the equation. -19x + 13y + -13y + 4z = 0 + -13y Combine like terms: 13y + -13y = 0 -19x + 0 + 4z = 0 + -13y -19x + 4z = 0 + -13y Remove the zero: -19x + 4z = -13y Add '-4z' to each side of the equation. -19x + 4z + -4z = -13y + -4z Combine like terms: 4z + -4z = 0 -19x + 0 = -13y + -4z -19x = -13y + -4z Divide each side by '-19'. x = 0.6842105263y + 0.2105263158z Simplifying x = 0.6842105263y + 0.2105263158z
| 15t^2+45t+10=40 | | -1/6(x-12)+1/2(x+2)=x+15 | | 1000+30m=e | | x^2+25x+11= | | -(5y+3)-(-4y-4)=-5 | | 20b-20b= | | (X-10)(X-10)+(X+10)(X+10)= | | .75x-1=12 | | (2x+8)(2x-8)= | | x^2+-11x+30= | | 16(3x-4)=4(12x+3) | | 21x-24x^2+6x=9-24x^2 | | 7+3s-4=7s+17-2s | | -3x+9=30 | | 6(3+2x)-3=51 | | 8z+11z=171 | | x/8=-29 | | -9.4x=65.8 | | -7(4b+3)+(29b-2)=0 | | 2(3-2r)=3 | | 1.2q-3.2-4.8q=-4.6q-1.2 | | 2x^2-3x-1= | | x+1/8=-1/4 | | p=75m-1000+30m | | s-49=-39 | | 19=y/8 | | 8e+3=e-3 | | 5y-20=3(y-2) | | p=105m-1000 | | 5m+2(m-3)=m+2 | | 6(5z-1)-4(z+3)=7(z+1) | | 0=-x^2+30x-150 |